The Joint Effect of Competitive Strategies, Competitive Advantage, Ethical Values, and Corporate Reputation on Performance of Accredited Universities in Kenya - Gathitu, Cecilia Wacuka; k’Obonyo, Peter; Machuki, Vincent N.; Njihia, James M. (Archives of Business Research, 2024)
The broad objective of the study was to determine the joint effect of competitive strategies, competitive advantage, ethical values and corporate reputation on performance of accredited universities in Kenya. The corresponding null hypothesis stated that the joint effect of competitive strategies, competitive advantage, ethical values and corporate reputation on performance of accredited universities in Kenya is not significantly different from the independent effects of predictor variables. This study was anchored on Industrial organization theory, Stakeholders’ theory, Resource-based theory and Virtue’s ethics theory. Descriptive cross-sectional survey was used. The population of the study comprised 53 accredited universities. To collect data, semi structured questionnaires were administered online while a few were dropped and picked later. Data was analyzed using regression models. Findings from the test of hypotheses showed that the joint effect of competitive strategies, competitive advantage, ethical values and corporate reputation on performance was significantly different from the independent effects of predictor variables and thus the null hypothesis was rejected. The study outcomes contributed to theory, policy, and management practice where policy makers in higher education and university managers were recommended to establish a policy framework that observes ethical practices; quality programs, reliable training, research and adoption of competitive strategies such as market penetration, strategic alliances, product development focus, differentiation and cost leadership. A single respondent was deemed to introduce bias in choosing responses and was a limitation to the study. However, use of questionnaires reduced subjectivism in responses. For generalizability of results Longitudinal design was suggested for future studies.